SAMARKAND – A LIVING LEGACY - Ruzibayeva Gulbakhor Kamol kizi (Web of Journals Publishing, 2024)
Samarkand is a historic city in Uzbekistan, has long been known as a cultural crossroad and a key hub along the ancient Silk Road. This article explores the unique cultural and historical significance of Samarkand, focusing on its role as a center of cultural exchange, learning and architectural splendor. By examining the city’s diverse influences, historical landmarks and its modern-day role in educational tourism, this article aims to highlight the importance of Samarkand as a living testament to the convergence of civilizations.
Keywords: Samarkand, Silk Road, cultural crossroads, Timurid architecture, educational tourism, Central Asia.